Aplikasi Campuran Ekstrak Kulit Nanas dan Biji Pepaya sebagai Biokoagulan untuk Penurunan Fe, Mn, dan Kekeruhan pada Air Asam Tambang dengan Metode Jar Test - Ismi Khairunnissa Ariani; Rina Noor Hayati; Riza Hudayarizka; Cut Keumala Banaget; Krisma Nabilla (LPPM ITK, 2025)
Acid mine drainage can pollute the environment if not treated properly. Acid mine drainage can be treated using the coagulation-flocculation jar test method with pineapple peel and papaya seed biocoagulants to reduce the contaminants contained therein. The purpose of this study was to determine the characteristics of acid mine drainage, analyze the effect of biocoagulant dosage and analyze the variation of slow stirring time in reducing Fe, Mn, Turbidity parameters in Acid Mine Drainage. The research variables used were biocoagulant dosage of 0.5 - 2.5 gr/500 mL and slow mixing time of 10 - 30 minutes. Based on the characteristic test, acid mine drainage has content that exceeds the quality standard. The optimum biocoagulant dose was 0.5 gr/500 mL with Fe parameter removal efficiency of 66.56% with a concentration of 18.3 mg/L, Mn of 8.71% with a concentration of 12.78 mg/L, and Turbidity of 78.87% with a concentration of 5.33 NTU. The optimum stirring time is 10 minutes with Fe removal efficiency of 61.71%, Mn of 71.18%, and Turbidity of 63.12%.